Adversity Quotient, Self Efficacy dan Lingkungan Bagi Kegiatan Kewirausahaan Mahasiswa Berbasis Teknologi - Nuraeni; Murtiadi Awaluddin; Mutakallim (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2022)
This study aims to (1) determine the effect of the simultaneous adversity quotient, self- efficacy and environment on technology-based entrepreneurial intentions (technopreneurs) in Islamic banking students at FEBI UIN Alauddin Makassar; (2) To determine the effect of partial adversity quotient, self-efficacy and environment on the intention of technology- based entrepreneurship (technopreneur) in Islamic banking students at FEBI UIN Alauddin Makassar. This research uses descriptive and explanatory research methods. Primary data was obtained from respondents through the distribution of online questionnaires to 60 students. To test the hypothesis, a structural equation model was used with the help of the AMOS 22 application. The results of the analysis show that (1) the adversity quotient has a positive and significant influence on entrepreneurial intentions; (2) self-efficacy has a positive and significant influence on entrepreneurial intentions; (3) The environment has a positive and significant influence on entrepreneurial intentions; (4) adversity quotient, self efficacy and the environment have a positive and significant influence on entrepreneurial intentions.